Functional characterization of a common XIa inhibitory Kunitz-domain Shp4 from nine schistosoma secreted proteins with diverse C-terminal fragments. - Xiangdong Ye; Xiaolin Deng; Huanhuan Gao; Shuwen Chen; Li Ding; Fang Sun; Chenhu Qin; Hongyi Luo; Wen Zhu; Xudong Luo; Zongyun Chen (PLoS Neglected Tropical Diseases, 2025)
Coagulation factor XIa is a drug target for new anticoagulants, but no XIa inhibitors have been found from schistosoma, a worm living in the bloodstream. In this study, by sequence blasting and structural fold searching of Kunitz-domain containing proteins from schistosoma, a specific Kunitz-domain Shp4 that appears in nine secreted proteins from four schistosoma species was identified successfully. Functional studies showed that Shp4 is a novel XIa inhibitor with a Ki value of 3.35 nM, which inhibited coagulation factor XIa activity in a non-heparin-dependent manner. His-pull-down assay further indicated the direct interaction between Shp4 and XIa. Animal experiments showed that Shp4 is a useful peptide lead drug with well antithrombotic effects in vivo. Alanine-scanning experiments showed that R18 is the key residue for XIa inhibitory and anticoagulation activities. Structural modelling of nine schistosoma-derived full-length secreted proteins suggested that the C-terminal non-Kunitz-domain fragments might play important roles in modulating the Kunitz-domain functions by steric hindrance effect and transmembrane helix structure. In conclusion, our work characterized the first XIa inhibitor from schistosoma with high anticoagulation activity and well antithrombotic effects, and highlights a potential strategy to modulate the Kunitz-domain, not only by the functional loop, but also by diverse C-terminal fragments.